1992
DOI: 10.5059/yukigoseikyokaishi.50.451
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Functions of the Sugar Chains of Glycoproteins.

Abstract: Most proteins within living organisms contain sugar chains. Recent advancements in cell biology have revealed that many of these sugar chains play important roles as signals for cell-surface recognition phenomena in multi-cellular organisms. In order to elucidate the biological information included in the sugar chains and link them with biology, a novel scientific field called 'glycobiology' has been established. This review will give an outline of the analytical techniques for the structural study of the suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
4

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 2 publications
2
52
0
4
Order By: Relevance
“…N-glycosylation has widely been reported to exert significant effects on several properties of glycoproteins, including antigenicity, solubility, protein folding, protease resistance, pharmacokinetics or biological activity (Schauer 1988;Kobata 1992;Yusa et al 2005). Moreover, sialylation is known to be able to influence the in vivo circulatory lifetime of these proteins, which is crucial to their therapeutic value (Dordal et al 1985;Takeuchi et al 1989;Imai et al 1990;Misaizu et al 1995;Koury 2003;Yuen et al 2003;Elliott et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…N-glycosylation has widely been reported to exert significant effects on several properties of glycoproteins, including antigenicity, solubility, protein folding, protease resistance, pharmacokinetics or biological activity (Schauer 1988;Kobata 1992;Yusa et al 2005). Moreover, sialylation is known to be able to influence the in vivo circulatory lifetime of these proteins, which is crucial to their therapeutic value (Dordal et al 1985;Takeuchi et al 1989;Imai et al 1990;Misaizu et al 1995;Koury 2003;Yuen et al 2003;Elliott et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The soluble receptor was treated with AT-glycosidase F and the oligosaccharides released were analyzed by matrix-assisted laser desorption mass spectrometry, which showed that the protein carried six types of short carbohydrate chains. The predominant species was a hexasaccharide of molecular mass 1,039, containing a fucose subunit linked to the proximal IV-acetylglucosamine residue:Keywords: glycoprotein; glycosylation sites; insect cell-type glycosylation; soluble interferon y receptor Most native proteins carry carbohydrate moieties that fulfill important functions, some of which are still not well understood.Protein glycosylation shows a high structural diversity, and this might be responsible far the diverse and complex roles carbohydrates play in biological and clinical aspects (Paulson, 1989;Goochee et al, 1991;Kobata, 1992;Sharon & Lis, 1993). Development of carbohydrate-based drugs and glycotechnology products in general relies on information derived from recent advances in glycobiology that contributed to elucidation of important carbohydrate functions, like cell-ceJI interaction, protein turnover, protein transport, and others.…”
mentioning
confidence: 99%
“…The functional biological activity of the glycoprotein is directly affected by glycosylation, including its trafficking and folding within the host cell (Scallon et al 2006;Walsh and Jefferis 2006;Willey 1999). Once secreted, solubility, aggregation, stability and immunogenicity of the protein may be affected by its glycosylation pattern (Kobata 1992;Sinclair and Elliott 2005;Willey 1999;Wyss and Wagner 1996). N-glycosylation is initiated in the ER, and O-glycosylation can be initiated in either the ER or Golgi apparatus, but due to processing inconstancies glycans can have frequent structural heterogeneities (Patel et al 1992;Seth et al 2006a;Varki 1998).…”
Section: Optimisation Of Glycosylation Patternsmentioning
confidence: 99%